Electromagnetic scattering simulation-based design and optimization of feature indices for visual roughness measurements. (17th October 2019) - Liu, Jian; Xiong, Yan; Lu, Enhui; Yang, Dezhi; Yuan, Yijie
Abstract: In this letter, we develop an electromagnetic scattering simulation-based method for designing the indices for grinding surfaces roughness measurement. Based on the simulation data, the index design and index optimization do not require a large number of sample blocks and imaging experiments. This makes the proposed method time-saving and low-cost compared with the original experimental methods. The results of the simulations are verified through experiments. This demonstrates that the electromagnetic scattering simulations can be used to design and optimize the characteristic indices for visual roughness measurements.